Public Expenditure Handbook : A guide to public expenditure policy issues in developing countries - Chu, Ke-young; Hemming, Richard (Washington, D.C. : Government Expenditure Analysis Division, Fiscal Affairs Dept., International Monetary Fund, 1991)
The handbook represents an attempt to discuss policy issues within the framework that combines both the macroeconomic and microeconomic aspects of public expenditure
Includes bibliographical references.
osc 13/06/17
Loans
Keywords: Government spending policy; Developing countries